Tinjauan Literatur Dampak Psikologis Pascabencana Banjir pada Masyarakat DKI Jakarta - Gadis Eka Fitri Sibarani; Desy Safitri; Sujarwo Sujarwo (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
Flooding is one of the most frequent disasters in DKI Jakarta and contributes not only to physical and economic losses but also to the emergence of various psychological problems among affected communities. This study aims to analyze the psychological impacts of post-flood disasters, particularly among vulnerable groups such as children and the elderly, and to examine the effects of repeated flood exposure on mental health conditions. This study employs a literature review method with a qualitative descriptive approach through the identification and synthesis of relevant scientific sources. Data analysis was conducted using content analysis to identify patterns, relationships, and trends in research findings. The results indicate that flooding is associated with psychological disorders such as stress, anxiety, depression, and post-traumatic stress disorder (PTSD), with varying levels of severity. Repeated exposure to flooding has been shown to increase individuals’ vulnerability to mental health problems and reduce psychological well-being. However, protective factors such as social support, religiosity, emotional regulation abilities, and adaptive coping strategies play a significant role in strengthening resilience and accelerating psychological recovery. The findings highlight the importance of a holistic disaster management approach that integrates mental health services, strengthens community capacity, and enhances preparedness education to improve the psychological resilience of flood-affected communities.